Village Economic Development Model Based on Village-Owned Enterprises (BUMDes): A New Insight from North Sumatera-Indonesia - Ade Isyana Hairunnisa; Erlina Erlina; Sirojuzilam Sirojuzilam; Rujiman Rujiman (Budapest International Research and Critics University, 2021)
This study aims to determine the factors that influence village economic development based on Village-Owned Enterprises (BUMDes) by looking at the relationship between the influence of human resources (HR), capital participation, governance, and rural area planning on the development of the village economy based on BUMDes in the Regency /City of North Sumatera. The research method used is quantitative research conducted by survey, namely research in which the data is collected from a population sample to represent the entire population. The entire population was given a research questionnaire, amounting to 53 BUMDes in the Regency / City of North Sumatera. The number of questionnaires distributed was 512, with nine respondents for each BUMDes and 498 returned questionnaires. After processing the data with SmartPLS, the research results show that human resources, capital participation, governance, and regional planning partially have a significant effect on developing the BUMDes-based village economy.